Building the strategy for recruiting key employees in th milk food joint stock company the period of 2019-2024 = Xây dựng chiến lược tuyển dụng nhân lực chủ chốt cho Công ty Cổ phần Thực phẩm Sữa TH giai đoạn 2019-2024 - Nguyễn, Đình Tuấn (2020)
Apart from the abstract, acknowledgment, content table, abbreviations list, reference, the content of the thesis is structured in 4 chapters: Theoretical background on recruitment strategies in enterprises ; Research methods & designs ; Analyzing factors & current situation of the company that affects to the recruitment strategies for key employees in THMF ; Building a recruitment strategy on key employees in THMF JSC from 2019 to 2024